Innovation and Misoneism during the Reign of Emperor Yoḥannǝs IV (1872–1889) - Pankhurst, Richard (Aethiopica, 2005)
The article attempts to examine the character and extent of innovation and misoneism during the reign of Yoḥannǝs, i.e. the period between the largely frustrated aspirations of Tewodros and of more substantial achievements of Mǝnilǝk. The study suggests that the reign of Yoḥannǝs in fact witnessed changes in many fields of life. These included improvements in communication between Ethiopia and the outside world; the advent of new imports; changes in land tenure and class relations; the strengthening of church land-holding; attempted action against slavery and the slave trade; increasing diffusion of fire-arms; the forced conversion of Muslims, and prohibition of foreign missionaries; the banning of tobacco; the depletion of wild-life; the introduction of a national flag, the appointment of a foreign consul abroad, and the building of a church in Jerusalem.